Reproduction Status and Population Dynamic of Kuantan Cattle in the Kuantan Singingi Regency - Yendraliza Yendraliza; M Rodiallah; T Astuti; Elfawati Elfawati (Indonesian Center for Animal Research and Development (ICARD), 2020)
The purpose of this study was to determine reproductive efficiency, population dynamics, natural increase and estimated output of the Kuantan cattle in the Kuansing Regency, Province of Riau. A total of 311 Kuantan cattle and 99 Kuantan cattle farmers were used in this study through a survey study. Respondent samples were taken from seven districts. Data sampling using purposive sampling with survey methods. Data collection was carried out by interviewing farmers and observing and was analyzed descriptively. Parameters measured were reproductive efficiency, natural increase, estimated output and population dynamics of Kuantan cattle. Results showed that the reproductive efficiency of Kuantan cattle was 1.04%, natural increase 5.14%, the balance of male and female 1: 5, the value of male NRR 50% and female NRR 100.56%, total cattle out 18.69% and total incoming cattle 18.69%, output value 48.88% and estimated population dynamics 2.85%. In conclusion, Kuantan cattle reproduction has not been efficient with the natural increase of the Kuantan cattle was very low, and the replacement stock availability for male and female cattle has not been fulfilled. It is recommended not to release Kuantan cattle in the next 5 years to maintain population balance.